Relationship between shoulder roll and hand propulsion in the front crawl stroke - Kudo, S.; Sakurai, Y.; Miwa, T.; Matsuda, Y. (Journal of Sports Sciences, 2017)
This study re-evaluated the magnitude of hand propulsion (HP) in the pull and push phases of the front crawl stroke and investigated the association between the angular velocity of shoulder roll (SR) and hand propulsive lift (HPL). SR was computed in the plane normal to a forward direction for 16 skilled swimmers performing the front crawl stroke at a maximal sprinting pace. HP, hand propulsive drag (HPD) and HPL were determined by a dynamic pressure approach. HP and HPD in the pull phase were greater than in the push phase (P < 0.05) while HPL in the pull phase was similar to that in the push phase. Eleven swimmers out of the 16 swimmers had a significant within-swimmers correlation between OmegaSR and HPL in the push phase (P < 0.05). That is, HPL increased in the push phase as the OmegaSR of rolling back to the neutral position became faster. A swimmer should use more drag for hand propulsion in the pull phase and propulsion from drag and lift equally in the push phase. Based on the relationship between OmegaSR and HPL in the push phase, a possible stroke technique to enhance HPL using OmegaSR is discussed.